Consumer protection on the Polish banking market according to European Union regulations - Przytuła, Katarzyna (Journal of Finance and Financial Law, 2019)
With the development of banking services and the technologies used in it, there is a need to educate consumers about the effective and safe use of the products offered. The aim of the article is to show the activities carried out by the European Union and the state preventing threats to market participants. The results of conducting European consumer policy and the level of consumer knowledge about the financial market were also discussed.